2016
DOI: 10.1186/s12862-016-0596-1
|View full text |Cite
|
Sign up to set email alerts
|

Rab32 and Rab38 genes in chordate pigmentation: an evolutionary perspective

Abstract: BackgroundThe regulation of cellular membrane trafficking in all eukaryotes is a very complex mechanism, mostly regulated by the Rab family proteins. Among all membrane-enclosed organelles, melanosomes are the cellular site for synthesis, storage and transport of melanin granules, making them an excellent model for studies on organelle biogenesis and motility. Specific Rab proteins, as Rab32 and Rab38, have been shown to play a key role in melanosome biogenesis. We analysed the Rab32 and Rab38 genes in the tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…41 This would be difficult to reconcile with the fact that RAB32 and RAB38 are paralogs. 14,15 Using 2 different RAB32 antibodies, we found no evidence for this long form of the protein.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…41 This would be difficult to reconcile with the fact that RAB32 and RAB38 are paralogs. 14,15 Using 2 different RAB32 antibodies, we found no evidence for this long form of the protein.…”
Section: Discussionmentioning
confidence: 70%
“…RAB proteins are key mediators of vesicular trafficking. RAB38 and the closely related molecule RAB32 14,15 are expressed in a tissue-specific manner and have been proposed to confer cell-type specificity on LROs, notably on melanosomes. 10,11,16 This is consistent with the phenotype of the fawn-hooded rat, one of the first rodent models of HPS.…”
Section: Introductionmentioning
confidence: 99%
“…MC1R is another key gene for melanin synthesis, and its mutations have been found to have significant association with the extended black trait of ducks (Yu et al, 2013). In addition to the well-known candidate genes mentioned above, MLANA, RAB38, OCA2, TSPAN10, and MSLN were also reported to incorporate into the process of melanin synthesis (Lu et al, 2010;Coppola et al, 2016;Seberg et al, 2017;Béziers et al, 2019). The result showed that the difference on the dorsum and ventral side of LBM ducks might be caused by the mRNA expression changes of multi melanin synthesis related genes.…”
Section: The Melanin Synthesis Related Genes Is the Main Cause Of Dormentioning
confidence: 99%
“…The RAB38 gene is highly expressed in melanocytes, and RAB38 protein co-localizes with end-stage melanosomes 12,13 . RAB38 participates in the transport of newly synthesized tyrosinase and Tyrp1, which are key enzymes in melanin production from the trans-Golgi network endosomes to maturing melanosomes 14,15 . Mutations in RAB38 gene were previously described in the dilution of coat colour in chocolate (cht) mice 12 and Ruby rats 13 .…”
Section: Discussionmentioning
confidence: 99%